An Assessment of the Remote Procedure Call Mechanism - Birrell, Andrew (Proceedings of the 5th ACM SIGOPS European workshop: Models and paradigms for distributed systems structuring, 1992)
For more than ten years, many people (including myself) have been advocating the use of "Remote Procedure Calls" (RPC) as the primary technique for communication among the components of a distributed system. Many researchers have explored the design space for RPC, and they have writtenmany worthy papers on what they discovered. Many commercial vendors have constructed and purveyed RPC systems. Many standards committees have added their own distinctive values to the enterprise. Where has all this effort got us?
Le mont Saint Michel